2018
DOI: 10.1007/s00153-018-0609-4
|View full text |Cite
|
Sign up to set email alerts
|

Generic variations and NTP $$_1$$ 1

Abstract: We prove a preservation theorem for NTP 1 in the context of the generic variations construction. We also prove that NTP 1 is preserved under adding to a geometric theory a generic predicate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Finally, the fact that T * feq2 is NSOP 1 follows from an unpublished result of Ramsey that NSOP 1 is preserved by the generic variation construction from [3] (the analogous statement for NTP 1 was shown by Dobrowolski in [10]).…”
Section: Examplesmentioning
confidence: 70%
“…Finally, the fact that T * feq2 is NSOP 1 follows from an unpublished result of Ramsey that NSOP 1 is preserved by the generic variation construction from [3] (the analogous statement for NTP 1 was shown by Dobrowolski in [10]).…”
Section: Examplesmentioning
confidence: 70%
“…In [CP98], the problem of adding a generic unary predicate symbol was studied, where such an expansion is called the generic predicate construction. We know that NTP 2 is preserved by the generic predicate construction by [Che14] and NTP 1 by [Dob18], whose idea of the proof is similar as [Che14]. Utilizing ideas there, we show in Section 5 that NATP is preserved under such a construction.…”
Section: Introductionmentioning
confidence: 81%
“…Finally, T ∩ is interpretable in the theory of equality. Dobrowolski [Dob18] showed that T * Var is NTP 1 when T is NTP 1 . It is conjectured that NSOP 1 and NTP 1 are equivalent.…”
Section: Examplesmentioning
confidence: 99%